Assessing the Impact of Pharmaceutical Contamination in Malaysian Groundwater: Risks, Modelling, and Remediation Strategies - Lie, Michael; Rubiyatno; Binhudayb, Faisal Saud; Thao, Nguyen Thi Thanh; Kristanti, Risky Ayu (Tropical Aquatic and Soil Pollution, 2024)
Pharmaceuticals in Malaysia’s groundwater are a growing concern as they can potentially affect the environment and human health negatively. Pharmaceuticals are found in abundance in groundwater from sources such as septic tanks, leachates from landfills, wastewater effluents from pharmaceutical-related industries, medical institutions, wastewater treatment plants, and households, agriculture runoff and leakage of effluent wastes in Malaysia. Pharmaceutical contaminant usually travels through advection and dispersion from waterways or soil into the groundwater. The mathematical model of the advection-dispersion equation and enzyme-linked immunosorbent assay (ELISA) are analysed for the prediction of movement and concentration of pharmaceuticals.  Furthermore, the evolution of pharmaceuticals in the environment, living organisms and human health is assessed. Pharmaceuticals have found their way into the food chain and exhibit toxicity and hazard to aquatic ecosystems. However, the toxicity of pharmaceuticals to humans is still not yet much to be researched although strong evidence of possible negative consequences. Moreover, remediation technologies such as activated carbon adsorption, activated sludge, anaerobic treatment and advanced oxidation process are discussed for the mitigation of pharmaceuticals contamination.